Precision surgical education - Luis Carlos Domínguez Torres; Neil Valentín Vega Peña; Álvaro Enrique Sanabria Quiroga (Federación Colombiana de Obstetricia y Ginecología, 2024)
Information and data are accelerating the implementation of competency-based medical education. The adoption of precision education can contribute to this purpose. This article discusses the extent to which precision surgical education can be used in assessing the minimum reliability standards of future surgeons - given the advent of Entrustable Professional Activities - and as an option to strengthen the career trajectory of residents.